PEMBERDAYAAN KADER: BAKSOS TERAPI ANAK UNTUK OPTIMALISASI TUMBUH KEMBANG - Sri Kustiyati; Wahyuningsih, Istiqomah Risa (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Abstract The terms growth and development actually include two events that are different in nature, but interrelated and difficult to separate, namely growth and development. The purpose of this activity is to train cadres about massage therapy in children and then continue by holding a child therapy social service. Outputs: scientific articles in be-ISSN community service journals. First stage: Training with the target is cadre mothers to be trained in child therapy with the Aikipressure method. Second stage: Conducting child therapy social services to provide opportunities for cadres who have been trained to apply the knowledge gained during training, with assistance. Baby massage social service activities have been carried out at the Asyifa Kartopuran Surakarta Clinic on Sunday, June 4, 2023 which was attended by 24 infant and toddler patients. This activity was fully supported by the Asyifa Clinic team. Baby massage social service activities can provide benefits to the community, especially in increasing bonding attachment in the family and helping to overcome health problems in infants. In addition, knowledge and skills about infant massage are also important for mothers and health cadres to have so that they can perform infant massage independently and effectively.